Factors influencing blood pressure variability in postmenopausal women: evidence from the China Health and Nutrition Survey - Zhonge Tao; Quanxin Qu; Jing Li; Xiaolin Li (Clinical and Experimental Hypertension, 2023)
Background The aim is to identify the factors influencing blood pressure variability in postmenopausal women based on the China Health and Nutrition Survey (CHNS). Material and Methods The data on postmenopausal women between 1993 and 2015 were extracted from the CHNS. Group-based trajectory modeling was used to analyze the development track of blood pressure changes, based on which the subjects were separately divided into two groups for systolic blood pressure (SBP) and diastolic blood pressure (DBP). Univariate and multivariate analyzes were performed to analyze the factors influencing SBP and DBP. Results A total of 346 women were eligible for the study. Group-based trajectory modeling showed two different trajectories of blood pressure, including the low-level, slowly developed type and the high-level, rapidly developed, stable type of SBP, as well as the low-level, slowly developed type and the high-level, slowly developed type of DBP. In multivariate analysis, age (odds ratio [OR]: 1.118, 95% confidence interval [CI]: 1.082–1.156), body mass index (BMI) (OR: 2.239, 95%CI: 1.010–4.964), antihypertensive agents (OR: 7.293, 95%CI: 2.191–24.275), hip circumference (OR: 1.069, 95%CI: 1.014–1.128) and marital status (OR: 3.103, 95%CI: 1.028–9.361) were found to be the significant factors influencing SBP; age (OR: 1.067, 95%CI: 1.039–1.096), alcohol consumption (OR: 2.741, 95%CI: 1.169–6.429), antihypertensive agents (OR: 4.577, 95%CI: 1.553–13.492), hip circumference (OR: 1.093, 95%CI: 1.049–1.138), and marital status (OR: 3.615, 95%CI: 1.228–10.644) were the predominant factors influencing DBP. Conclusions In postmenopausal women, age, BMI, antihypertensive agents, hip circumference, and marital status are associated with SBP changes, while age, alcohol consumption, antihypertensive agents, hip circumference, and marital status with DBP variability. MeSH Keywords postmenopausal women, blood pressure, development track, influencing factors, CHNS